A scaling relationship between power and shear for Bernoulli pads at equilibrium. (17th October 2022) - Tomar, Anshul S.; Kamensky, Kristina M.; Mejia-Alvarez, Ricardo; Hellum, Aren M.; Mukherjee, Ranjan
Abstract: Abstract : Bernoulli pads can create a significant normal force on an object without contact. The radial outflow which creates this force also imposes a significant shear force on the object. Better understanding this shear force can improve pad designs in order to mitigate material deformation and damage, or allow the pads to be used as shear-based cleaning implements. Here, we use computational fluid dynamics to explore the parameter space and show a power-law relationship between the fluid power at the pad inlet and the maximum shear stress. These simulations are validated by a particle tracking velocimetry experiment. A relationship between the maximum shear stress and the inlet Reynolds number is provided, and some implications of the observed scaling relationships are explored.